The Role of Teachers in Enhancing Children's Self-Confidence at TK IT Al-Kiswah, Bengkulu City - Noviana Dewi; Ayu Wulandari; Fidhia Andani (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Self-confidence is one of the fundamental aspects of social-emotional development in early childhood that significantly influences children's ability to engage in social interaction, academic tasks, and daily life activities. Teachers, as the primary figures in the educational environment, play a pivotal role in nurturing and enhancing children's self-confidence. This study aims to analyze and describe in depth the role of teachers in increasing children's self-confidence at TK IT Al-Kiswah, Bengkulu City. This research employs a qualitative descriptive approach with data collection techniques consisting of participatory observation, semi-structured interviews, and documentation. The subjects of this study were three classroom teachers and 20 children aged 5–6 years in Group B. Data analysis was conducted using Miles and Huberman's interactive model encompassing data reduction, data display, and conclusion drawing/verification. The findings of this study reveal that teachers at TK IT Al-Kiswah carry out four main roles in developing children's self-confidence, namely as motivators, guides, facilitators, and evaluators. These roles are implemented through various strategies, including providing verbal and non-verbal praise, applying scaffolding approaches, using innovative and play-based learning methods such as role-playing, storytelling, singing, and demonstrating artwork. The supportive learning environment, combined with active collaboration between teachers and parents, also makes a significant contribution to children's self-confidence development. This research emphasizes the importance of teachers' professional competence and a holistic educational ecosystem in optimizing the growth of self-confidence in early childhood.